STRATEGY FOR DEVELOPING THE RAINBOW BRIDGE MARINE TOURISM OBJECT IN NAGARI MUARA KANDIS PUNGGASAN PESISIR SELATAN DISTRICT : Strategi Pengembangan Objek Wisata Bahari Jembatan Pelangi Di Nagari Muara Kandis Punggasan Kabupaten Pesisir Selatan - Lala Gusti Ayu; Aldri Frinaldi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The purpose of this study is to develop the Rainbow Bridge marine tourism object in order to increase the local original income (PAD) of Muara Kandis Punggasan and the economy of the surrounding community by analyzing strategies then using the right strategies. The background of this study is the failure in the development of rainbow bridge marine tourism objects in Nagari Muara Kandis, Punggasan, South Coast Regency and how the strategy in developing these tourist attractions. The research method uses a type of descriptive qualitative research with data analysis techniques in the form of SWOT analysis. Data collection through observation, interviews and documentation. The result of this study is that the Rainbow Bridge marine tourism object is known to the public not only with the uniqueness of the bridge and the beauty of the beach but also provided a children's playground that made many visitors at that time, but this tourist attraction is no longer operating until now, even photo spots in marine attractions are no longer there or damaged. Many facilities had to be added, especially after the attraction's vacuum, all average facilities had to be reorganized. The failure of the construction of the Rainbow Bridge marine tourism object was due to lack of management, especially Nagari Owned Enterprises (BUMNAG), besides that this tourist attraction was also quiet because it was hit by Covid-19 at that time.